Globalization and the British Council`s Cultural Policy through ELT: Ghana and Egypt Compared - Amel BELADJOUZ; Pr. Mustapha GASMI (bibliotheque Amar Telidji University of Laghouat, 2023)
Over the past few decades, there has been a growing interest in teaching English language. As a result, many countries have been striving to teach English through various organizations, institutions, and programs. Furthermore, with the acceleration of globalization, English has become a widely spoken global language. As a result, most people have chosen to learn this language. Moreover, in recent research globalization has been linked to the U.S.A as a global superpower. Therefore, most research relates English as a global language to the U.S.A. Nevertheless, English as a global language has been linked to the British Empire as a global power in the nineteenth and twentieth centuries and it expanded worldwide chiefly in the British colonies and protectorates. Along this line of thought, the purpose of this study is twofold. First, it examines and compares U.S. educational programs and the British Council in English language teaching within the context of Globalization. Second, through this comparison, the study strives to analyze whether there is a causal-effect relationship between U.S. educational programs within the context of globalization and the British Council`s cultural policy in ELT in Ghana and Egypt using the causal-comparative method. Two questionnaires were used as a research instrument, the first was for the Ghanaian students and teachers, and the second was for the Egyptian ones. A sample of 388 respondents participated in the collection of data. This study uses mixed-method research focusing on a quantitative approach with SPPS software for the analysis of the questionnaires. After the analysis of the gathered data from both questionnaires and based on previous theories and studies, the major findings of this study revealed that the presence of globalization and U.S. educational programs have not affected the British Council`s cultural policy in English language teaching in the British former colony Ghana and protectorate Egypt. Accordingly, the second part of the results revealed that after comparing the British Council in Ghana and Egypt, it was found that VI the British Council Egypt is the most highly reputable and popular in ELT rather than British Council Ghana. Summing up, this study found that the attraction and influence of the British Council`s cultural policy in English language teaching abroad and in its former colonies and protectorates remains strong reflecting the UK`s position on the world stage. Keywords: Egypt, English language teaching, colonies, protectorates, Ghana, global language, Globalization, the British Council, U.S. educational programs.